AUTOMATISASI NAVGATE PADA SISTEM NOTAM PIA WILAYAH - Metha Yurike Cartika; Elfi Amir; Endang Sugiharti; Rini Sadiatmi; Dini Wagini; Togi Adnan Maruli Sinaga; Novita Ayu Permatasari; Moch Faisal Muzaki; Muh Hasbullah (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
In providing aeronautical information services, AIS needs a system that can be used to make PIA's work easier, one of which is Navgate. So it is important to pay attention to innovation in developing the Navgate system optimally in order to create a comfortable work environment for PIA to work. Innovation is needed in this feature so that it can avoid human error in work and make PIA's work easier in distributing NOTAMs. Developing the necessary features can influence the comfort of personnel work, so that it can make personnel work effective.